Green synthesis, structure–activity relationships, in silico molecular docking, and antifungal activities of novel prenylated chalcones - Godara, Rajni; Kaushik, Parshant; Tripathi, Kailashpati; Kumar, Rakesh; Rana, Virendra Singh; Kumar, Rajesh; Mandal, Abhishek; Shanmugam, V.; Pankaj,; Shakil, Najam Akhtar (Frontiers in Chemistry, 2024)
A series of 16 novel prenylated chalcones (5A-5P) was synthesized by microwave-assisted green synthesis using 5-prenyloxy-2-hydroxyacetophenone and different benzaldehydes. Comparisons were also performed between the microwave and conventional methods in terms of the reaction times and yields of all compounds, where the reaction times in the microwave and conventional methods were 1–4 min and 12–48 h, respectively. The synthesized compounds were characterized using different spectroscopic techniques, including IR, 1H-NMR, 13C-NMR, and LC-HRMS. The antifungal activities of all compounds were evaluated against Sclerotium rolfsii and Fusarium oxysporum under in vitro conditions and were additionally supported by structure–activity relationship (SAR) and molecular docking studies. Out of the 16 compounds screened, 2’-hydroxy-4-benzyloxy-5’-O-prenylchalcone (5P) showed the highest activity against both S. rolfsii and F. oxysporum, with ED50 of 25.02 and 31.87 mg/L, respectively. The molecular docking studies of the prenylated chalcones within the active sites of the EF1α and RPB2 gene sequences and FoCut5a sequence as the respective receptors for S. rolfsii and F. oxysporum revealed the importance of the compounds, where the binding energies of the docked molecules ranged from −38.3538 to −26.6837 kcal/mol for S. rolfsii and −43.400 to −23.839 kcal/mol for F. oxysporum. Additional docking parameters showed that these compounds formed stable complexes with the protein molecules.